Environmental Aspects of a Potential Philippines-European Union Free Trade Agreement - Antonio G.M. La Vi\~A±a; Lai-Lynn Angelica B. Barcenas; Carla Lesaca; Liezel Bobadilla (Philippine Institute for Development Studies (PIDS), 2014)
This paper focuses on the environmental aspects of a potential Philippines-European Union Free Trade Agreement (PH-EU FTA). Potential environmental issues in the negotiation of such an FTA (if at all undertaken) are identified to better prepare the Philippine negotiating panel and equip them with information and analysis to make well-informed positions on such issues. It looks at the interaction between the multilateral trade regime - the World Trade Organization (WTO) principally - and multilateral environmental agreements, reviews the Philippine approach to environment-related trade measures, and looks at Philippine practice and implementation of environmental agreements from a trade perspective. EU policies on trade, environment, and development are also discussed to anticipate what could be EU positions during the FTA negotiations with the Philippines.The paper ends with the following conclusions and recommendations: (1) The EU will most likely push for more harmonization of the FTA provisions with WTO rules. On the sustainable development front, the EU would push for including sustainable development principles into all levels and in cross-cutting policy areas; (2) The Philippines can expect the EU to come up with a strong position on sustainable development, expecting the Philippines to make concrete commitments to principles of sustainable development; (3) Philippine sustainable development goals are not inconsistent with the EU. However, the Philippines in the FTA negotiations would be best served to emphasize poverty reduction and financial and technical support from its EU partners.
Keywords: 330; Philippines; trade and sustainable development; multilateral environmental agreements; trade and environment; Philippine practice of international environmental law; conflict between trade and environment